Using Point-of-Choice Prompts to Reduce Sedentary Behavior in Sit-Stand Workstation Users - Larouche, Miranda L.; Mullane, Sarah L.; Toledo, Meynard John L.; Pereira, Mark A.; Huberty, Jennifer L.; Ainsworth, Barbara E.; Buman, Matthew P. (Frontiers in Public Health, 2018)
Introduction: Desk-based office workers are at occupational risk for poor health outcomes from excessive time spent sitting. Sit-stand workstations are used to mitigate sitting, but lack of workstation usage has been observed. Point-of-choice (PoC) prompts offer a complementary strategy for office workers to break up their sitting time. Study purpose: The purpose of this study was to examine the preliminary efficacy, preference, and acceptability of a theory-driven (i.e., 40 unique prompts encompassing social cognitive theory; TD-PoC) and an atheoretical basic reminder PoC prompt intervention (R-PoC) on reducing sedentary behavior in office workers with self-reported low sit-stand workstation usage (≤4 h per day). Methods: In a cross-over design, participants (N = 19, 78.9% female, 39.4 ± 10.7 years of age) completed a 5-days no-prompt control condition followed by a random and counterbalanced assignment to one of the TD-PoC and R-PoC active conditions with a 1-week washout period between. Preliminary efficacy was assessed during work hours with the activPAL micro accelerometer. Preference was assessed prior to each active condition and acceptability was assessed following each active condition via questionnaire. Results: The R-PoC prompt condition significantly decreased sitting time (b[se] = −49.0 [20.8], p = 0.03) and increased standing time (b[se] = 49.8 [19.7], p = 0.02) and displayed a significant increase in sit-stand transitions (b[se] = 2.3 [1.1], p = 0.04), relative to no-prompt control. Both the R-PoC and TD-PoC prompt conditions significantly decreased time spent in prolonged sitting bouts at b[se] = −68.1 [27.8], (p = 0.02), (b[se] = −76.7 [27.1], p = 0.008) relative to no-prompt control. Overall, the TD-PoC prompt condition displayed higher preference and acceptability ratings; however, these differences were not significant (p's > 0.05). Conclusion: While the R-PoC prompt condition was slightly more efficacious than the TD-PoC prompt condition, the TD-PoC prompt condition was rated with higher preference and acceptability scores. Large variations between participants in preference, acceptability, and intervention feedback may indicate need for tailored messaging which may facilitate sustained use in the long-term.